Seleção e caracterização de estirpes de Bacillus thuringiensis efetivas no controle da traça-das-crucíferas Plutella xylostella Selection and characterization of Bacillus thuringiensis strains effective to control the diamondback moth Plutella xylostella - Patrícia Teles Medeiros; Márcio do Nascimento Ferreira; Érica Soares Martins; Ana Cristina Menezes Mendes Gomes; Rosana Falcão; José Manoel Cabral de Souza Dias; Rose Gomes Monnerat (Pesquisa Agropecuária Brasileira, 2005)
O objetivo deste trabalho foi selecionar e caracterizar, no Banco de Germoplasma de Bacillus spp., da Empresa Brasileira de Pesquisa Agropecuária, as estirpes de Bacillus thuringiensis mais tóxicas à Plutella xylostella, por métodos morfológicos, bioquímicos e moleculares. Das 203 estirpes testadas, sete causaram 100% de mortalidade e foram semelhantes à estirpe padrão utilizada, B. thuringiensis subsp. kurstaki. Elas apresentaram proteínas de 130 kDa e 65 kDa, presença de genes cry1 e cry2 e cristais bipiramidais, cubóides e redondos. As estirpes selecionadas oferecem novas perspectivas de controle de P. xylostella. The aim of this work was to select and characterize the most toxic Bacillus thuringiensis strains, from the Germplasm Bank of Bacillus spp. of Empresa Brasileira de Pesquisa Agropecuária, against Plutella xylostella. Strains were characterized by morphological, biochemical and molecular methods. It was observed that seven out of the 203 strains tested showed high toxicity compared to the standard used B. thuringiensis subsp. kurstaki (HD-1), which showed 100% mortality. Selected strains showed features described for lepidoptera regarding the protein of 130 kDa and 65 kDa; profile and features were obtained through the PCR reactions, making possible to identify the presence of cry1 and cry2 genes. Moreover, the scanning electron microscopy showed the bipiramydal, cubed and round crystal forms. The selected strains offer new perspectives to control P. xylostella.